Behavior of cooperative banking in Portugal: the resilience of Crédito Agrícola in the 2007-2018 period - Faria, Artur (2022)
The financial system is a fundamental pillar in the efficient functioning of credit to the economy. The financial crisis had an impact on the entire financial system, making it clear that the banking sector in general must necessarily undergo a process of change in strategy, namely in the moderate granting of credit. Through a comparative analysis of cooperative banking with other commercial banking, for the period 2007 to 2018, we conclude that, in Portugal, cooperative banking - represented by the Integrated System of Mutual Agricultural Credit - was more resilient to the economic and sovereign debt crisis, due to its conservative transformation ratio, which allowed it to achieve positive results and not to degrade its capital ratios. The application of the HEAT! and z-score methodologies shows that, in the most acute period of the crisis, Crédito Agrícola's indicators diverge favourably from those of other commercial banks, placing Crédito Agrícola as one of the banking institutions with the lowest risk of insolvency. Therefore, liquidity and long-term orientation, which are characteristics of cooperative banking, are essential for its stability and contribute to the financial soundness of the whole system.